2023
DOI: 10.3390/catal13111390
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Insights into Carbon Dioxide Hydrogenation over Bimetallic Iron–Cobalt Catalysts: A Density Functional Theory Study

Dilan Tuncer,
Ali Can Kizilkaya

Abstract: The conversion of carbon dioxide to fuels and chemicals is a promising long-term approach for mitigating CO2 emissions. Despite extensive experimental efforts, a fundamental understanding of the bimetallic catalytic structures that selectively produce the desired products is still lacking. Here, we report on a computational surface science approach into the effect of the Fe doping of Co(111) surfaces in relation to CO2 hydrogenation to C1 products. Our results indicate that Fe doping increases the binding stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Lastly, the top-down approach often leads to the generation of a high number of oxygen functionalities on carbon surfaces, which negatively affect CO2 hydrogenation over structured zeolites due to the formation of oxy-carbides [70]. Tuncer and Kizilkaya [71] revealed that the topdown method of Fe doping on Co(111) surfaces suppresses oxygen eviction from cobalt surfaces, forming oxide phases on bimetallic FeCo catalysts, hence, potentially restricting hydrogenation reactions. Heo and Park [72] presented that the thermal reduction process is capable of removing oxygen functionalities, thus increasing CO2 affinity and uptake on the carbon surfaces.…”
Section: Top-down Approachmentioning
confidence: 99%
“…Lastly, the top-down approach often leads to the generation of a high number of oxygen functionalities on carbon surfaces, which negatively affect CO2 hydrogenation over structured zeolites due to the formation of oxy-carbides [70]. Tuncer and Kizilkaya [71] revealed that the topdown method of Fe doping on Co(111) surfaces suppresses oxygen eviction from cobalt surfaces, forming oxide phases on bimetallic FeCo catalysts, hence, potentially restricting hydrogenation reactions. Heo and Park [72] presented that the thermal reduction process is capable of removing oxygen functionalities, thus increasing CO2 affinity and uptake on the carbon surfaces.…”
Section: Top-down Approachmentioning
confidence: 99%